Assessing Teacher Competency and Preparedness for Integrating Digital Media in 21st-Century Education: An Exploratory Review - Lailan Aprina Siregar; Surianti Siregar (STAI Hubbulwathan Duri, 2024)
The integration of digital media in 21st-century education is critical, yet understanding teacher competency and readiness remains a challenge. This study investigates teacher digital literacy, readiness, and barriers to integrating digital media in education, proposing actionable strategies for improvement. A qualitative multi-case study design was employed. Data were collected through semi-structured interviews, focus group discussions, and document analysis with 30 teachers from SMK N 1 Lubuk Barumun, selected via purposive sampling to ensure diverse representation. Thematic analysis was conducted to identify patterns and insights. Findings reveal significant disparities in digital literacy levels, influenced by individual teaching experiences. Many teachers lack essential digital skills and confidence, while professional development programs often emphasize theory over practical application. Infrastructure inadequacies and limited institutional support further hinder effective digital media integration. However, access to resources and fostering a collaborative culture within schools significantly enhance implementation efforts. These findings highlight the necessity of a multifaceted approach to bridge the competency gap. This includes targeted professional development, infrastructural investment, and fostering institutional support to empower educators in rural and urban settings. The study concludes that addressing the barriers to digital media integration requires comprehensive efforts at multiple levels. Future research should focus on hands-on training programs for educators in rural schools and scalable infrastructural solutions to enhance digital literacy. This study contributes to the broader discourse on leveraging institutional support to overcome digital literacy challenges in education.